2008
DOI: 10.1021/jp801042p
|View full text |Cite
|
Sign up to set email alerts
|

A Microwave and Quantum Chemical Study of Cyclopropanethiol

Abstract: The microwave spectra of cyclopropanethiol, C(3)H(5)SH, and one deuterated species C(3)H(5)SD, have been investigated in the 20 - 80 GHz frequency range. The spectra of the ground vibrational state and of three vibrationally excited states of the parent species of a conformer which has a synclinal ("gauche") arrangement for the H-C-S-H chain of atoms, was assigned. The H-C-S-H dihedral angle is 76(5)° from synperiplanar (0°). The b-type transitions of the ground and of the vibrationally excited states of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…CCSD/cc-pVTZ values top row. MP2/cc-pVTZ values bottom row in parentheses and in italics. c Reference . d Reference . e Reference . f Reference . g Reference . h MP2/aug-cc-pVTZ values ref . i Reference . j MW, ref . …”
Section: Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…CCSD/cc-pVTZ values top row. MP2/cc-pVTZ values bottom row in parentheses and in italics. c Reference . d Reference . e Reference . f Reference . g Reference . h MP2/aug-cc-pVTZ values ref . i Reference . j MW, ref . …”
Section: Results and Discussionmentioning
confidence: 99%
“…The Møllendal group has reported the microwave spectrum of cyclopropanethiol (CP–SH) and found that the molecule has two equivalent synclinal conformers. They also reported the ground-state torsional energy level splitting to be 1.664 MHz.…”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The present study also represents an extension of our recent investigations of the conformational properties of thiols such as 3-butyne-1-thiol (HSCH 2 CH 2 CCH), ( Z )-3-mercapto-2-propenenitrile (HSCHCHCN), cyclopropanethiol (C 3 H 5 SH), and 2,2,2-trifluoroethanethiol CF 3 CH 2 SH, using MW spectroscopy augmented with quantum chemical calculations.…”
Section: Introductionmentioning
confidence: 97%